1992
DOI: 10.1152/jn.1992.68.3.767
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and glutamate agonists stimulate neuron-specific expression of Fos-like protein in the striatum

Abstract: 1. The monoamine dopamine and the amino acid glutamate are major neurotransmitters in the basal ganglia implicated in the normal functions of the striatum and in extrapyramidal disease states. To study the effects of these neurotransmitters on gene transcription in striatal neurons, we treated rats with dopamine (monoamine) agonists and with glutamate agonists and monitored the induction of Fos-like protein in striatal neurons. We administered the indirect monoamine agonists cocaine and amphetamine intraperito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
123
0
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(135 citation statements)
references
References 0 publications
11
123
0
1
Order By: Relevance
“…A similar gradient was seen both in the high-affinity dopamine uptake system demonstrated in the normal non-dopamine-depleted animal (Marshall et al, 1990) and in the levels of expression of D, receptors following 6-OHDA (Joyce,199 1). Interestingly, Graybiel and coworkers conclude from double labeling experiments that direct or indirect dopamine agonists do not induce c-fos-like proteins in the cholinergic intemeurons of the striatum (Graybiel, 1991;Berretta et al, 1992). The expression of c-fos in the CS cholinergic neurons following MFB transection may be related more to the consequences of the transection on the levels of CS dopamine than to the ability to activate specific dopamine receptor subtypes pharmacologically (see below).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar gradient was seen both in the high-affinity dopamine uptake system demonstrated in the normal non-dopamine-depleted animal (Marshall et al, 1990) and in the levels of expression of D, receptors following 6-OHDA (Joyce,199 1). Interestingly, Graybiel and coworkers conclude from double labeling experiments that direct or indirect dopamine agonists do not induce c-fos-like proteins in the cholinergic intemeurons of the striatum (Graybiel, 1991;Berretta et al, 1992). The expression of c-fos in the CS cholinergic neurons following MFB transection may be related more to the consequences of the transection on the levels of CS dopamine than to the ability to activate specific dopamine receptor subtypes pharmacologically (see below).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both these experiments and those of other groups do not take into account the presence of other types of dopamine receptors reported in the striatum (Civelli, 199 1). Graybiel and colleagues also have shown that c-&s-positive neurons in the dopamine-depleted CS following acute cocaine and amphetamine treatment contain DARPP-32, a marker of the D, receptor, and that there is no C-$X response detectable in the GABA/enkephalin-containing neurons (Graybiel, 199 1;Berretta et al, 1992). The GABA/enkephalin-containing neurons project through an interneuron in the GP to the STN forming one branch of the subthalamic loop (Gerfen, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…pathway neurons (Berretta et al, 1992;Cenci et al, 1992;Johansson et al, 1994;Kosofsky et al, 1995;Badiani et al, 1999), especially with higher doses (Uslaner et al, 2003;Ferguson et al, 2004) as used here. However, recent studies showed that factors such as novelty can enhance c-fos induction by psychostimulants also in the indirect pathway (Badiani et al, 1999;Uslaner et al, 2003;Ferguson et al, 2004).…”
Section: Evidence For Molecular Changes In the Direct Pathway Associamentioning
confidence: 99%
“…23 This may be because amphetamine induces release of DA from nerve terminals via activation of the D1 receptor. 24,25 In rat striatum lesioned with 6-OHDA, the density of Fos-positive nuclei is lower than normal and can be restored by intrastriatal transplants of DA tissue. [26][27][28] We tested whether Ad-NSE-GDNF affected the release of DA by striatal fibers by injecting control rats (OHDA, empty-Ad) and Ad-NSE-GDNF-treated rats with amphetamine (5 mg/kg, i.p.).…”
Section: In Vitro Experimentsmentioning
confidence: 99%